Advanced cell‐based modeling of the royal disease: characterization of the mutated F9 mRNA. (25th September 2017) - Martorell, L.; Luce, E.; Vazquez, J.L.; Richaud‐Patin, Y.; Jimenez‐Delgado, S.; Corrales, I.; Borras, N.; Casacuberta‐Serra, S.; Weber, A.; Parra, R.; Altisent, C.; Follenzi, A.; et al.
Abstract : Essentials The Royal disease (RD) is a form of hemophilia B predicted to be caused by a splicing mutation. We generated an iPSC‐based model of the disease allowing mechanistic studies at the RNA level. F9 mRNA analysis in iPSC‐derived hepatocyte‐like cells showed the predicted abnormal splicing. Mutated F9 mRNA level was very low but we also found traces of wild type transcripts. Summary: Background: The royal disease is a form of hemophilia B (HB) that affected many descendants of Queen Victoria in the 19th and 20th centuries. It was found to be caused by the mutation F9 c.278‐3A>G. Objective: To generate a physiological cell model of the disease and to study F9 expression at the RNA level. Methods: Using fibroblasts from skin biopsies of a previously identified hemophilic patient bearing the F9 c.278‐3A>G mutation and his mother, we generated induced pluripotent stem cells (iPSCs). Both the patient's and mother's iPSCs were differentiated into hepatocyte‐like cells (HLCs) and their F9 mRNA was analyzed using next‐generation sequencing (NGS). Results and Conclusion: We demonstrated the previously predicted aberrant splicing of the F9 transcript as a result of an intronic nucleotide substitution leading to a frameshift and the generation of a premature termination codon (PTC). The F9 mRNA level in the patient's HLCs was significantly reduced compared with that of his mother, suggesting that mutated transcripts undergo nonsense‐mediated decay (NMD), a cellular mechanism that degrades PTC‐containing mRNAs. We also detected small proportions of correctly spliced transcripts in the patient's HLCs, which, combined with genetic variability in splicing and NMD machineries, could partially explain some clinical variability among affected members of the European royal families who had lifespans above the average. This work allowed the demonstration of the pathologic consequences of an intronic mutation in the F9 gene and represents the first bona fide cellular model of HB allowing the study of rare mutations at the RNA level.